Integrasi Aliran Pemikiran Keislaman: Pemikiran Qadariyah dan Jabariyah yang Bersandar Dibalik Legitimasi Al-Qur’an - Suhaimi Suhaimi (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2019)
Abstract: This article is deliberately adopted by the author in order to deepen the scientific treasures related to the problems of thought of schools that have developed in the post-Prophet Muhammad era, especially Qadariyah and Jabariyah. Besides that, the writer is also interested in the thoughts of the two schools that are in extreme conflict. The Qadariyah sect argues that humans have the freedom to desire and do deeds, nothing to do with God's will. But instead Jabariyah argues differently, that humans do not have any power and will, all because of God's will. Therefore, these two opposing opinions need integration of ideas so that they can be found at the meeting point. The method used in this article is carried out by reviewing the literature relating to the history of Qadariyah and Jabariyah thoughts which are then carried out in an objective and subjective interpretation. Keywords: Qadariyah, Jabariyah and Thought Integration.